A Study of Farmers Buddy App Development - Haseemun, P; Somasekhar, K (International Journal of Computer Sciences and Engineering, 2025)
: Agriculture is a way of life, a tradition, which, for centuries, has shaped the thought, the outlook, the culture and economic life of the people of India. The advent of modern technologies at the beginning of the last century has brought in development of various technologies, which has substantially increased the yields of various crops.It is an agricultural portal which gives solutions to the farmers and students of agricultural studies in India. Farmers Buddy aims to disseminate useful information about improved technology to the farming community and service providers in the rural areas. The major focus of Agriculture sector presently in the in this portal, is pertaining to Agricultural Credit, Policies & Schemes, Agricultural Bank loans, Market Information, Agricultural Best Practices, On & Off Farm Enterprises and various Products & Services.